KEMAMPUAN TUMBUHAN AIR SEBAGAI AGEN FITOREMEDIATOR LOGAM BERAT KROMIUM (Cr) YANG TERDAPAT PADA LIMBAH CAIR INDUSTRI BATIK - Upit Ratna Puspita; Asrul Sahri Siregar; Nuning Vita Hidayati (Berkala Perikanan Terubuk, 2011)
Batik Industry has been developed in Banyumas regency, Central JavaIndonesia. This industry produced liquid waste as the side of production process.The liquid waste decreased the water quality surrounds it. One of the pollutantwhich brought trough the liquid waste was heavy metal chromium (Cr) whichknown toxic to the organism in the water. Therefore, there should be preventionaction to minimize the bad impact of liquid waste. One of method which could beuse to prevent the water quality was by phytoremediation. There were three kindsof aquatic plant in this research; Eceng gondok (Eichornia crassipes), kayu apu(Pistia stratiotes) and ganggang (Hydrilla verticillata). The aim of using aquaticplant was to observe the ability of aquatic plant to decrease chromium level in thewater and decide which was the most effective. It was use completely randomizeddesign with 4 treatments and 6 repetitions, which will analyze by ANAVA andcontinued with LSD. The result showed that aquatic plant could be used asremediator agent to heavy metal Cr. Eceng gondok had 49.56%, kayu apu had33.61% and ganggang had 10.84% on decreasing Cr level in liquid waste of batikindustry. It can conclude that Eceng gondok was the most effectivephytoremediator agent on decreasing Cr level in liquid waste of batik industry.